2022
DOI: 10.1021/acs.joc.1c02606
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzo[b]thiophenes via Electrophilic Sulfur Mediated Cyclization of Alkynylthioanisoles

Abstract: A stable dimethyl(thiodimethyl)sulfonium tetrafluoroborate salt was employed for the electrophilic cyclization reaction of o-alkynyl thioanisoles for the synthesis of 2,3-disubstituted benzo[b]thiophenes. The reaction described herein works well with various substituted alkynes in excellent yields, and a valuable thiomethyl group was introduced with ease. The reaction utilizes moderate reaction conditions and ambient temperature while tolerating various functionalities. To elucidate the mechanism, electrophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In 2022, Kesharwani and coworkers reported an electrophilic cyclization of 2-alkynylthioanisoles 53a using commercially available and stable 1,1,2-trimethyldisulfan-1-ium tetrafluoroborate 53b as the thiomethyl electrophile at ambient temperature (Scheme 53). 75 The protocol was compatible with a variety of alkynes bearing terminal aryl, alkyl, vinyl and silyl groups but was ineffective for those bearing secondary and tertiary propargyl alcohols.…”
Section: Reaction Of 2-alkynylthioanisoles/2-alkynylselenoanisolesmentioning
confidence: 99%
“…In 2022, Kesharwani and coworkers reported an electrophilic cyclization of 2-alkynylthioanisoles 53a using commercially available and stable 1,1,2-trimethyldisulfan-1-ium tetrafluoroborate 53b as the thiomethyl electrophile at ambient temperature (Scheme 53). 75 The protocol was compatible with a variety of alkynes bearing terminal aryl, alkyl, vinyl and silyl groups but was ineffective for those bearing secondary and tertiary propargyl alcohols.…”
Section: Reaction Of 2-alkynylthioanisoles/2-alkynylselenoanisolesmentioning
confidence: 99%
“…[15] Recently Kesharwani and coworkers found that DMTSF could promote the cyclization of o-alkynyl thioanisoles, providing a new method to synthesize 3-sulfenylated benzo [b]thiophene products (Scheme 2C). [16] We have recently investigated the application of DMTSM in the activation of alkyl alkynes. [17] The reactivity of this electrophilic agent in the presence of deactivated alkynes have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Dithioacetal derivatives with internal enol silyl ether, vinyl silane or allylstannane have been investigated in the synthesis of cyclic carbon rings, using DMTSF as the initiator (Scheme 2B) [15] . Recently Kesharwani and coworkers found that DMTSF could promote the cyclization of o ‐alkynyl thioanisoles, providing a new method to synthesize 3‐sulfenylated benzo[ b ]thiophene products (Scheme 2C) [16] . We have recently investigated the application of DMTSM in the activation of alkyl alkynes [17] .…”
Section: Introductionmentioning
confidence: 99%
“…43 In the present year, Kesharwani and co-workers reported the application of DMTSF to promote the electrophilic activation and internal cyclization of alkynyl thioanisoles. 44 In the continuation of our program 45−48 considered exploring its reaction with alkynes, which would offer a direct activation and addition strategy for the sulfenotriflation of alkynes with a readily available and easyto-handle thiolating reagent (Scheme 1c). Herein we present our findings on the direct addition of DMTSM to various terminal alkynes and haloalkynes, providing access to βmethylthio vinyl triflates under extremely simple conditions.…”
mentioning
confidence: 99%
“…It has been found that by anodic oxidation, symmetrical alkynes can undergo difunctionalization via thiirenium ion intermediates (Scheme b) . In the present year, Kesharwani and co-workers reported the application of DMTSF to promote the electrophilic activation and internal cyclization of alkynyl thioanisoles . In the continuation of our program and looking to expand the new synthetic applications of DMTSM, we considered exploring its reaction with alkynes, which would offer a direct activation and addition strategy for the sulfenotriflation of alkynes with a readily available and easy-to-handle thiolating reagent (Scheme c).…”
mentioning
confidence: 99%